2020
DOI: 10.1007/s40262-020-00925-8
|View full text |Cite
|
Sign up to set email alerts
|

Model-Informed Precision Dosing of Everolimus: External Validation in Adult Renal Transplant Recipients

Abstract: Background and Objective The immunosuppressant everolimus is increasingly applied in renal transplantation. Its extensive pharmacokinetic variability necessitates therapeutic drug monitoring, typically based on whole-blood trough concentrations (C 0). Unfortunately, therapeutic drug monitoring target attainment rates are often unsatisfactory and patients with on-target exposure may still develop organ rejection. As everolimus displays erythrocyte partitioning, haematocrit-normalised wholeblood exposure has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Similarly, others showed that tacrolimus, MPA, everolimus, creatinine and iohexol can be quantified reliably in VAMS samples with haematocrit values between approximately 0.20 and 0.60 43,48,58 . As haematocrit values outside these ranges are seldomly encountered in adult kidney transplant recipients, 93 also in the clinically unstable phase, this probably allows for DBS‐ and VAMS‐based monitoring without pronounced haematocrit interference for most patients. Nevertheless, DBS‐ and VAMS‐based monitoring should still be considered carefully in the first weeks after transplantation and in otherwise clinically unstable patients, as these studies set their maximum tolerable haematocrit effect thresholds at ±15%, which still allows for substantial haematocrit‐dependent assay variability.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Similarly, others showed that tacrolimus, MPA, everolimus, creatinine and iohexol can be quantified reliably in VAMS samples with haematocrit values between approximately 0.20 and 0.60 43,48,58 . As haematocrit values outside these ranges are seldomly encountered in adult kidney transplant recipients, 93 also in the clinically unstable phase, this probably allows for DBS‐ and VAMS‐based monitoring without pronounced haematocrit interference for most patients. Nevertheless, DBS‐ and VAMS‐based monitoring should still be considered carefully in the first weeks after transplantation and in otherwise clinically unstable patients, as these studies set their maximum tolerable haematocrit effect thresholds at ±15%, which still allows for substantial haematocrit‐dependent assay variability.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, others showed that tacrolimus, MPA, everolimus, creatinine and iohexol can be quantified reliably in VAMS samples with haematocrit values between approximately 0.20 and 0.60. 43,48,58 As haematocrit values outside these ranges are seldomly encountered in adult kidney transplant recipients, 93…”
Section: Discussionmentioning
confidence: 99%
“…Following the publication of a recent PopPK model for everolimus AUC estimation, integrating previous exposure, 23 we checked whether taking into account anteriorities could improve AUC estimation. For this, we selected the patients with at least two requests (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Bayesian prior) and compared to the new ML models. For a posteriori evaluation, individual PK parameter estimates, as opposed to population PK parameter estimates, can be used to generate a posteriori predictions (the Bayesian posterior), and compared to the prev ML models [44][45][46]. All used ML models provide deterministic predictions.…”
Section: Concentration Prediction Evaluationmentioning
confidence: 99%